2018
DOI: 10.1016/j.jpor.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Is zirconia a viable alternative to titanium for oral implant? A critical review

Abstract: Zirconia implants are a promising alternative to titanium with a superior soft-tissue response, biocompatibility, and aesthetics with comparable osseointegration. However, further long-term longitudinal and comparative clinical trials are required to validate zirconia as a viable alternative to the titanium implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 100 publications
1
120
0
7
Order By: Relevance
“…Commercially pure titanium is the most widely used material in implant dentistry, but a search for alternatives has been ongoing for decades. Yttria-stabilized zirconia does appear to meet all important requirements as patients and dentists increasingly seem to prefer metal-free solutions (Sivaraman, Chopra, Narayan, & Balakrishnan, 2018). This trend is driven by growing concerns among patients about titanium sensitivity, allergies, or intolerance, even though there is scarcely any evidence that these factors might be clinically relevant (Fage, Muris, Jakobsen, & Thyssen, 2016;Hosoki, Nishigawa, Miyamoto, Ohe, & Matsuka, 2016;Thomas, Iglhaut, Wollenberg, Cadosch, & Summer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially pure titanium is the most widely used material in implant dentistry, but a search for alternatives has been ongoing for decades. Yttria-stabilized zirconia does appear to meet all important requirements as patients and dentists increasingly seem to prefer metal-free solutions (Sivaraman, Chopra, Narayan, & Balakrishnan, 2018). This trend is driven by growing concerns among patients about titanium sensitivity, allergies, or intolerance, even though there is scarcely any evidence that these factors might be clinically relevant (Fage, Muris, Jakobsen, & Thyssen, 2016;Hosoki, Nishigawa, Miyamoto, Ohe, & Matsuka, 2016;Thomas, Iglhaut, Wollenberg, Cadosch, & Summer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Together with its antibacterial effect, ZrO 2 7 may prevent peri-implant bone resorption and periimplant soft inflammation. 23 Moreover, it was previously shown that ZrO 2 coatings may promote adhesion and spreading of progenitor cells and bone-forming cells, i.e. osteoblasts.…”
mentioning
confidence: 99%
“…Zirconia with better optical, aesthetic, mechanical and biological qualifications, is a hopeful substitute to traditional Ti implant system for oral recovery [61][62][63][64], and is produced by the oxidation of zirconium [25,27,[65][66][67]. Zirconium, which is a transition metal [56,68] with greywhite color [69][70][71][72][73], can be used to make zirconia implant.…”
Section: Zirconia Implantsmentioning
confidence: 99%